2017
DOI: 10.1038/s41598-017-04870-8
|View full text |Cite|
|
Sign up to set email alerts
|

Human neutrophils phagocytose and kill Acinetobacter baumannii and A. pittii

Abstract: Acinetobacter baumannii is a common cause of health care associated infections worldwide. A. pittii is an opportunistic pathogen also frequently isolated from Acinetobacter infections other than those from A. baumannii. Knowledge of Acinetobacter virulence factors and their role in pathogenesis is scarce. Also, there are no detailed published reports on the interactions between A. pittii and human phagocytic cells. Using confocal laser and scanning electron microscopy, immunofluorescence, and live-cell imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 39 publications
1
40
1
Order By: Relevance
“…It appears that A. baumannii is not recognized as a foreign body that stimulates a strong inflammatory response by neutrophils. However, this is clearly in contrast to the findings of other ( 39 ). Lazaro-Diez et al showed that A. baumannii is indeed phagocytosed by neutrophils and induces NET formation.…”
Section: Discussioncontrasting
confidence: 99%
“…It appears that A. baumannii is not recognized as a foreign body that stimulates a strong inflammatory response by neutrophils. However, this is clearly in contrast to the findings of other ( 39 ). Lazaro-Diez et al showed that A. baumannii is indeed phagocytosed by neutrophils and induces NET formation.…”
Section: Discussioncontrasting
confidence: 99%
“…The role of macrophages in eliminating A. baumannii remains controversial. Most studies showed that macrophages play a minor role during A. baumannii infection [ 14 , 15 , 21 ]. However, Qiu et al demonstrated that macrophages could be the first line of defense against respiratory A. baumannii infections; the depletion of alveolar macrophages significantly enhanced the susceptibility of mice to A. baumannii [ 22 ].…”
Section: A Baumannii and The Host Innate Immunmentioning
confidence: 99%
“…Early recruitment of neutrophils which take responsibilities in rapidly and continuously engulfing and killing bacteria is critical for initiating an efficient host defense against respiratory A. baumannii infection. [ 23 , 24 ] It was found that neutropenia was related to inhibited bacteria clearance, alteration of pro-inflammatory cytokine release thus leading to more severe microbial disease in A. baumannii infection. [ 25 , 26 ] In our study, at 6 h of A. baumannii administration, the recruitment of peripheral neutrophils sharply rose in mice with normal immunity.…”
Section: Discussionmentioning
confidence: 99%